Implementasi Etnomatematika Masyarakat Suku Anak Dalam (SAD) Kabupaten Batanghari Provinsi Jambi pada Pembelajaran Matematika - Muslimahayati Muslimahayati; Ambarsari Kusuma Wardani (Jurnal Elemen, 2019)
Indonesia has a diversity of cultures that describes its local wisdom. Culture in certain groups of people or tribes accompanied by mathematical activities was known as ethnomathematics. Ethnomathematics was not realized by the local community because it did not equip with definitions, theorems, or formulas. Therefore, the discussion of ethnomathematics becomes very interesting because it will enrich the treasures of science and also at the same time, preserve culture. One of the cultures introduced in this study is the culture of the Suku Anak Dalam Society (SAD), Batanghari Regency, Jambi Province. The Suku Anak Dalam (SAD) society is a typical ethnic group in Jambi Province. They are classified as ethnic minorities, namely social groups that have weak strength so that they are unable to influence the social system of the people in their territory. However, the SAD society also has ethnomathematics activities that need to be introduced. This research is qualitative research with an ethnographic approach which was analyzed according to Creswell's steps and used ethnographic methods which aim to produce findings in the form of mathematical activities in the Suku Anak Dalam (SAD) Batanghari Regency, Jambi Province.